Reconsidering “Community”: A Normative Model to Address Communities in the Law - Stern, Shai (Revue de droit de l'Université de Sherbrooke, 2020)
This article proposes a normative infrastructure concerning the legal treatment of communities in the law. This normative infrastructure, based on the state’s pluralistic obligation to protect the existence of multiple, diverse conceptions of good within a society, first requires the state to distinguish between different communities according to their characteristics to determine how each should be treated. This article suggests three key elements for distinguishing communities in this way: the social compatibility of the community with other communities and with society as a whole, the role that cooperation plays in the realization of the community’s conception of the good life, and the community’s political and economic strength.We then demonstrate how the proposed normative infrastructure should apply to various legal branches including private law (focusing on proprietary arrangements of residential communities and relational contracts); public law (aiming to provide a comprehensive policy to regulate the relationship between the liberal state and illiberal communities) and labor law (proposing a novel framework for rights and duties in workplaces).